Flipping a financial mathematics course in a higher education institution (HEI) - Lopes, Ana Paula (2018)
In the past few years, a new model for organizing the educational process in Higher Educational Institutions (HEI) arose and has been attracting the attention of many researchers and educators all over the world. This model, called “Flipped Classroom” or “Inverted Classroom”, is a pedagogical inversion of the traditional teaching paradigm: the main actions of the teaching and learning process that are used in classroom are now prepared by students previously before coming to class. As a result, when students come into class they already know what is the main issue and more important problems that will be under scope. Classroom is used to work on problems, advanced concepts, and engage in collaborative learning. This implies a much more active role for students and a more challenging mission for lecturers. The purpose of this paper is to present a Financial Mathematics Course in Polytechnic of Porto (P. Porto) that is using flipped classroom model as a pedagogical strategy. Moreover, it relates such strategy with active learning practices and discusses its effectiveness, investigating how the flipping affects student’s achievement and engagement in this course.